(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The city of Surat is considered as an art-silk Manchester of India. After Ahmedabad, it is second largest city of Gujarat state and is considered as a satellite town of Mumbai. The economy of the Surat city is highly reliant on the textile industry. This industry mainly operates in an unorganized way but provides employment to large mass and generates valuable FOREX for India. Due to the Fickle behavior of US dollar in Forex market and recession across the globe this textile has been affected to a great extent. The impacts of the global factors have positive and negative effect and the same has been studied in this research work.